Uterosacral ligament fibroid: a rare occurrence yet a major diagnostic challenge - Mishra, Tejasa; Jain, Madhu; Jain, Shivi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Fibroid is a common benign neoplasm more often located in the uterus and less commonly seen in the adnexa and other supporting structures of uterus like broad and uterosacral ligament. The incidence of extra uterine leiomyomas is <1%. A 48-year-old female para one live one presented with chief complaints of mass per abdomen for 2 years and prolonged heavy bleeding for 15 days. Based on the clinical and radiological findings, a diagnosis of tubo-ovarian mass was made. The patient underwent staging laparotomy. However, intraoperatively, she was diagnosed with uterosacral ligament fibroid of size approximately 40×45 cm. Total abdominal hysterectomy with bilateral salpingo-oophorectomy was done. There was no associated complication. Histopathology confirmed the mass to be leiomyoma. Uterosacral ligament fibroid is encountered very rarely. Our case report intends to bring to light the necessity of keeping the various possible locations of leiomyoma in mind and in considering adnexal mass as an important differential diagnosis of leiomyoma and vice-versa before operating. Leiomyoma is often confused with ovarian mass or neoplasm posing a diagnostic difficulty to a gynaecologist as well as radiologist thereby posing a challenge to the operating surgeon while performing surgery.